Alcalase-generated proteolysates of stone fish (Actinopyga lecanora) flesh as a new source of antioxidant peptides. Issue 1 (1st January 2018) - Bordbar, Sara; Ebrahimpour, Afshin; Zarei, Mohammad; Abdul Hamid, Azizah; Saari, Nazamid
ABSTRACT: In the present study, the alcalase-generated proteolysates obtained after 8 h of proteolysis of stone fish flesh showed the most potent antioxidant activity in terms of DPPH radical scavenging activity (77.43%, IC50 of 0.5 mg/mL), ABTS radical scavenging activity (92.73%, IC50 of 0.33 mg/mL) and FRAP value (39.2 mmol/100 mL FeSO4 ). These proteolysates profiled and characterized as antioxidative peptides. The proteolysates were initially subjected to ultrafiltration using MWCO Spin-X UF. Potent fractions were further characterized based on hydrophobicity using reversed-phase high-performance liquid chromatography (RP-HPLC) and isoelectric point using an OFFGEL isoelectric focusing fractionator. Results indicated that most of the antioxidative peptides found in fractions with a molecular weight (MW) of less than 2 kDa, hydrophilic (hydrophilicity >80%) and basic (p I  = 9.7). The final purified fraction with the highest antioxidant activity was selected for peptide identification and sequencing using Q-TOF mass spectrometry. A total of four peptides were identified, from which Peptide 1 (GVSGLHID) showed the highest antioxidant activity and this has potential as a novel bioingredient of nutraceuticals and functional foods to promote human health.